Bioconversion of agro‐industrial by‐products to lactic acid using Lactobacillus sakei and two Pediococcus spp. strains. (27th October 2016) - Juodeikiene, Grazina; Klupsaite, Dovile; Zadeike, Daiva; Cizeikiene, Dalia; Vidziunaite, Ieva; Bartkiene, Elena; Cernauskas, Darius
Summary: The aim of this study was to evaluate the bioconversion efficiency of rich in cellulose agro‐industrial by‐products such as wheat bran (WB), spent distiller's grain with solids (DGS), brewer's spent grain (BSG) and lupin ( Lupinus angustifolius L.) wholemeal fraction (LF) to lactic acid (LA) using acid tolerant lactic acid bacteria (LAB) strains Lactobacillus sakei KTU05‐06, Pediococcus acidilactici KTU05‐7 and P. pentosaceus KTU05‐9. Carbohydrase preparation Depol ™ 692L was used for the hydrolysis of non‐starch polysaccharides. Analysed raw materials were suitable substrates for LAB propagation and L‐lactic acid production. The lowest pH (3.6) was found in LF medium after 48 h fermentation with P. acidilactici and P. pentosaceus strains. The lowest pH (3.86) was measured in WB fermented with L. sakei, and in DGS and BSG (pH 3.8 and 3.9 respectively) fermented with P. acidilactici . The highest endoxylanase activity was excreted by the P. acidilactici and P. pentosaceus (84 and 69 XU g −1 respectively), and the highest α‐amylase activity was of L. sakei (255.6 AU g −1 ) after 24 h incubation in WB medium. The L‐lactic acid concentration of 86.11 g kg −1 was reached after the bioconversion of hydrolysed WB in combination with 48 h fermentation by P. pentosaceus KTU05‐9 strain. LA contents between 222 and 282 mg kg −1 was produced from lupin processing residues via fermentation using P. acidilactici and P. pentosaceus KTU05‐9 strains. The major challenge within the presented study is the viability of tested LAB in cereal waste media and effective LA production at a low pH (3.6 – 3.8). Abstract : Rich in cellulose agro‐industrial waste (wheat bran, spent distiller's grain with solids, brewer's spent grain) could be utilised to LA. The use of enzymatic hydrolysis and acid tolerant LAB increases the LA production effectiveness.